Design of an amphiphilic porphyrin exhibiting high in vitro photocytotoxicity. (4th January 2016) - Topkaya, Derya; Lafont, Dominique; Poyer, Florent; Garcia, Guillaume; Albrieux, Florian; Maillard, Philippe; Bretonnière, Yann; Dumoulin, Fabienne
Abstract : A promising photosensitiser, which exhibits extremely suitable properties for photodynamic applications is described. Abstract : A porphyrin monosubstituted by three triethyleneglycol chains grafted on a pentaerythritol skeleton was designed to display an optimized amphiphilicity for an enhanced cellular uptake and thus to exert enhanced photocytotoxicity. This porphyrin proved to be an excellent photosensitiser with submicromolar IC50 .